UMP publishes book on indigenous Semai tribe - UMP, PNC
Universiti Malaysia Pahang (UMP) officially launched its newly-published book entitled “Haknuk”, during the university’s Women Entrepreneurs Carnival at its Chancellery Square on June 16 last year.